2022
DOI: 10.1186/s12884-022-05270-1
|View full text |Cite
|
Sign up to set email alerts
|

Time to first antenatal care booking and its determinants among pregnant women in Ethiopia: survival analysis of recent evidence from EDHS 2019

Abstract: Background Antenatal care is one of the components of the maternal and child continuum of care. Timely booking ANC during pregnancy is of utmost importance to guarantee the best possible health outcomes for women and children. Inappropriate timing of the first ANC booking is associated with poor pregnancy outcomes, including perinatal death, stillbirth, and early neonatal death. According to WHO focused ANC recommendation, every mother should start booking ANC within the first 12 weeks of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…Our analysis found a downward SES trend in gestational age at first visit in both countries, with wealthier and more educated women more likely to initiate ANC earlier in pregnancy. This finding is similar to those found in other studies in Tanzania, 44 Ethiopia 45 and Nepal. 46 Prior research has identified cultural factors, uncertainty about pregnancy and lack of knowledge about ANC as additional contributing factors to late ANC initiation, 35 47 although we did not examine these in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis found a downward SES trend in gestational age at first visit in both countries, with wealthier and more educated women more likely to initiate ANC earlier in pregnancy. This finding is similar to those found in other studies in Tanzania, 44 Ethiopia 45 and Nepal. 46 Prior research has identified cultural factors, uncertainty about pregnancy and lack of knowledge about ANC as additional contributing factors to late ANC initiation, 35 47 although we did not examine these in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…The variance inflation factor (VIF) and tolerance values were used to check for the existence of multicollinearity between variables. A VIF above 4 or a tolerance below 0.25 indicated that multicollinearity might exist 45 46. To estimate the variation between clusters, proportional change in variance (PCV), intraclass correlation (ICC) and median odds ratio (MOR) were computed.…”
Section: Methodsmentioning
confidence: 99%
“…Variance inflation factor and tolerance value were used to check the exitances of multicollinearity between variables. A VIF above 4 or tolerance below 0.25 indicated multicollinearity might exist [ 27 ]. To estimate the variation between clusters, proportional change variance (PCV), intra-class correlation (ICC), and median odd ratio (MOR) were computed.…”
Section: Methodsmentioning
confidence: 99%